Living with systemic lupus erythematosus in South Africa: a bitter pill to swallow - Phuti, A. (Health Qual Life Outcomes, 2019)
BACKGROUND: Systemic lupus erythematosus (SLE) often has a profound negative impact on health-related quality of life (HRQoL). In the absence of any qualitative studies in sub-Saharan Africa, we undertook a study to explore living experiences, perceptions and unmet needs of South African patients with SLE. METHODS: Twenty-five women with SLE consented to participate in the study. They underwent individual in-depth interviews exploring their physical concerns, emotional health, sexual well-being and fertility. NVivo software was used for analysis. RESULTS: Participants were either of black ancestry or mixed racial ancestry, mainly indigent with only a quarter gainfully employed. Living with pain was the most common complaint, negatively impacting on activities of daily living (ADL), family expectations, social life, sleep and intimacy. Most participants expressed challenges of living with fatigue, and many felt their fatigue was misconstrued as being ‘simply lazy’. This pernicious fatigue had negative consequences on many facets of ADL, including caring for dependants, job sustainability and sexual well-being. All participants experienced low emotional states, often associated with suicidal ideations. Many experienced difficulties with fertility and childbearing and these were exacerbated in many instances by the pessimism of health care providers, resulting in confusion and depression. Physical disfigurements resulting from lupus-associated alopecia and rashes and corticosteroid-induced weight fluctuations were a major concern. These changes often affected self-image and libido, leading to strained personal relationships. Coping mechanisms that participants adopted included intense spiritual beliefs, ‘pushing through the difficult times’ and use of alternative therapies to relief symptoms was common. A poor understanding of SLE on the part of participant’s family and the community, coupled with the unpredictable course of the disease, exacerbated frustration and social exclusion. For most, limited income, lack of basic services, family dependencies, and comorbid diseases, such as human immune deficiency virus (HIV), exacerbated the daily negative SLE experiences. CONCLUSION: In this study of mainly indigent South African women, SLE is associated with complex, chronic and challenging life experiences. The chronic relapsing and unpredictable nature of the disease, poor understanding and acceptance of SLE, compounded by a background of poverty, inadequate social support structures, negatively impact on a range of personal, social and vocational daily life experiences. Improved access to psychosocial services and SLE education might result in better outcomes. TRIAL REGISTRATION: (Ethics Project identification code: 275/2016 and M160633 registered 10 & 29 August 2016).